Business Ethics In Islam - Sri Sukarningsih; Deliana Deliana (Proceeding International Seminar of Islamic Studies, 2019)
Business ethics is becoming something important today. Many cases of violations in the business world in the past that have had a negative impact have raised the importance of business ethics awareness. Islamic business ethics in every aspect of the company in terms of the implementation of the axioms of Islamic business ethics namely monotheism, balance, responsibility, free will, and virtue (ihsan). The application of Islamic business ethics has a positive impact on the entire operational process of the company. This is indicated by the results of the analysis of several aspects, namely aspects of marketing, management and human resources, legal, social, environmental impact, and financial aspects. The concept of business in Islam involves the concepts of wealth, income and material goods which belong to God, and humans only belong to Him. As a consequence, every Muslim has a responsibility to establish justice in society. Islamic business ethics has two inherent aspects namely honesty and fairness. The principle of honesty will give birth to various praiseworthy attitudes, namely: do not cover the defects of goods sold, do not commit fraud in buying and selling, do not commit gharar, and all kinds of transactions that are prohibited in Islam. While the principle of justice includes balance and responsibility. Balance in the world and the hereafter and responsibility to fellow human beings and responsibilities.